Pemberdayaan Masyarakat di Kota Padang dalam Pengelolaan Sampah Organik Berbasis Sirkular Ekonomi melalui Budidaya Maggot Black Soldier Fly (BSF) - Resti Rahayu; Fadjar Goembira; Robby Jannatan; Salbella Dwi Utari; Yona Afriani (Warta Pengabdian Andalas, 2025)
The issue of organic waste in Padang City is increasing due to the community's high activity level, which predominantly generates food waste. Currently, food waste accounts for 63% of the total waste in Padang City. The Black Soldier Fly (BSF) maggot is an effective agent for processing organic waste, requiring simple technology that is cost-efficient and easy to implement. BSF maggots also produce biomass with a high protein content that can be utilized as animal feed. The methods used in this study include socialization, education, direct field practice, and evaluation. The results demonstrated an increase in community understanding and interest in BSF maggot cultivation as a means to reduce organic waste. Participants also learned about the TOSS (Solid Waste Processing Technology at the Source) method for managing leaf and twig waste. This activity was expected to serve as a waste management model that reduces waste volume and creates opportunities within the circular economy, where organic waste is converted into valuable resources.